English Language Proficiency through the TOEFL Test Taken by UMNAW Postgraduate Students - Yugi Diraga Prawiyata; Ulian Barus (International Journal of English and Applied Linguistics (IJEAL), 2022)
The purpose of this research was to find out how the English proficiency of UMNAW postgraduate students was measured with the TOEFL test consisted of three main sections; Listening Comprehension, Structure and Written Expression, and Reading Comprehension. The researcher used a descriptive qualitative research design in which the researcher described and analyzed students’ English proficiency based on the TOEFL test. The fourth-year postgraduate students of the Indonesian Language Education Study Program in the Academic Year 2021/2022 total of 10 people the population of the research. Based on the research findings, it can be classified that in Listening Comprehension Section one student got the highest score 28 and one students got the lowest score of 18. In the Structure and Written Expression Section, one student got the highest score 24 and one student got the lowest score of 15. In Reading Comprehension Section, one student got the highest score 28 and one student got the lowest score of 19.  After being converted, one student got the highest score 453 and one student got the lowest score 440. Furthermore, it can be classified that UMNAW postgraduate students taking the TOEFL test are at a Low Intermediate level. This research is then expected to be a reference for further research and can be more perfectly developed.